150-year daily data (1870–2021) in lakes and rivers reveals intensifying surface water warming and heatwaves in the Pannonian Ecoregion (Hungary) - Huan Li; Jiang Sun; Quan Zhou; Mariusz Sojka; Mariusz Ptak; Yi Luo; Sirui Wu; Senlin Zhu; Viktor R. Tóth (Journal of Hydrology: Regional Studies)
Study region: Pannonian Ecoregion, Hungary. Study focus: Bridging the gap between atmospheric influences and aquatic environments, this study embarked on a comprehensive reconstruction of daily surface water temperatures across lakes and rivers within the Pannonian Ecoregion over an extensive period of 150 years (1870–2021). New hydrological insights for the region: The analysis revealed a clear warming trend in waters over the past 150 years, and majority of this warming occurred in recent three to four decades (average warming rate: 0.317 °C/decade). Seasonal patterns indicated that winter and spring exhibited faster warming rates, followed by autumn and summer. There has been a significant increase in the number, duration, and intensity of heatwaves in both lakes and rivers, particularly pronounced in the last 30–40 years, and with the rise of air temperatures, river and lake heatwaves tend to intensity. These findings underscore the escalating impact of climate change on freshwater systems in the Pannonian Ecoregion, emphasizing the urgent need for mitigation measures. As the first study on river and lake heatwaves in Hungary and one of the few studies on river heatwaves worldwide, this study will provide reference for analysing extreme thermal events in aquatic systems.